Black Cotaxtla-91 bean, a new seed variety for Veracruz regions. - López S., Ernesto (2016)
The most common black seeds employed by the farmers in Veracruz state are the small and dull black seed varieties. By the end of 1991, a new black bean seed variety was released for the tropical region, the black bean Cotaxtla-91. This variety had an average yield of 1477 kg/ha, compared with Jamapa and Negro Huasteco-81 varieties, which yielded 1252 and 1307 kg/ha respectively. These results were obtained from 1987 to 1990, as a result of 14 uniform field trials. The black bean, Cotaxtla-91, was bred at the Cotaxtla Experimental Station in 1983; obtained from a simple two line cross, the D- 149 by 1397. It was later improved by means of individual and mass selection procedures until a good uniformity, high yield and wide range of adaptabilily was obtained. This new variety has an undeterminated growth habit, a bush type plant with intermediate shoots and height fluctuating from 75 to 82 cm. The flowering starts around the 43th day and the harvesting period varies from 90-93 days after planting; this new variety is resistant to rust and shows tolerance to the presence of bean golde n mosaic virus (BGMV).